2015
DOI: 10.5198/jtlu.2015.824
|View full text |Cite
|
Sign up to set email alerts
|

The impact of walkable environment on single-family residential property values

Abstract: Abstract:Due to the impact of urban sprawl, the need for responsible property investing, and the emerging evidence supporting the linkage between walkable environment (in terms of built environment and walk accessibility) and residential property value, there is a critical need to develop systematic methodologies to quantify the impact of walkable environment on residential property value. This study provides a new generalized dissimilarity index for quantifying landuse mix, a key component of built environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…Cervero (2002) found that land-use diversity at origin and destination lowered the chance of private-vehicle usage, compared with public transport usage. Guo [13,14] used land-use mix and net residential density as factors to quantify the walkable environment.…”
Section: Case Context and Data Inputsmentioning
confidence: 99%
“…Cervero (2002) found that land-use diversity at origin and destination lowered the chance of private-vehicle usage, compared with public transport usage. Guo [13,14] used land-use mix and net residential density as factors to quantify the walkable environment.…”
Section: Case Context and Data Inputsmentioning
confidence: 99%
“…Tais evidências alinham-se com a literatura, que indica que valores venais do solo urbano aumentam com maiores níveis de caminhabilidade (28), no aumento dos valores de propriedades residenciais urbanas (29), especialmente em função de características da microescala como a presença e qualidade de calçadas.…”
Section: Resultados E Discussõesunclassified
“…Urban environments vary considerably in terms of the urban form, geographical and climatic conditions, types and amount of green elements, built form and use of materials, among others. Studies on residential liveability indicate that while various housing, neighbourhood and household characteristics determine the level of residential liveability, the impacts of these criteria as determinants of residential liveability tend to vary by housing types, land use mixes (Aurand, 2010;Song & Knaap, 2004), city block sizes, walkability (Brown et al, 2009;Guo et al, 2017), control (Lynch, 1981), identity and cultural and religious traditions; such a complex range tends to indicate that case specific studies are required to determine residential liveability to guide public policies. They also vary according to the region's social context (Balsas, 2004), political trends (Kaal, 2011;Teo, 2014), national lifestyles and the degree to which it is possible to live out of doors for much of the time.…”
Section: Liveabilitymentioning
confidence: 99%